2014
DOI: 10.7448/ias.17.1.19040
|View full text |Cite
|
Sign up to set email alerts
|

Utility of urine and serum lateral flow assays to determine the prevalence and predictors of cryptococcal antigenemia in HIV‐positive outpatients beginning antiretroviral therapy in Mwanza, Tanzania

Abstract: BackgroundDetection of subclinical cryptococcal disease using cryptococcal antigen screening among HIV-positive individuals presents a potential opportunity for prevention of both clinical disease and death if patients with detectable cryptococcal antigen are identified and treated pre-emptively. Recently developed point-of-care cryptococcal antigen tests may be useful for screening, particularly in resource-limiting settings, but few studies have assessed their utility.MethodologyThe objectives of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 22 publications
6
62
0
Order By: Relevance
“…The findings from this study were similar to recent prevalence reports from Namibia (3.3%) (Sawadogo et al, ) and Tanzania (3.7%) (Letang et al, ) and slightly lower than the prevalence reported in South Africa (4.3%) (Longley et al, ). However, lower than the prevalence reported in two studies from Nigeria (12.7% and 8.9%) (Oladele et al, ; Osazuwa, Dirisu, Okuonghae, & Ugbebor, ) and two more from Tanzania (7.1% and 5.1%) (Magambo et al, ; Wajanga et al, ). We also compared our finding with studies in other developing countries like Indonesia (7.1%) (Ganiem et al, ), Vietnam (4%) (Smith et al, ), and Thailand (9.2%) (Pongsai, Atamasirikul, & Sungkanuparph, ).…”
Section: Discussionmentioning
confidence: 71%
“…The findings from this study were similar to recent prevalence reports from Namibia (3.3%) (Sawadogo et al, ) and Tanzania (3.7%) (Letang et al, ) and slightly lower than the prevalence reported in South Africa (4.3%) (Longley et al, ). However, lower than the prevalence reported in two studies from Nigeria (12.7% and 8.9%) (Oladele et al, ; Osazuwa, Dirisu, Okuonghae, & Ugbebor, ) and two more from Tanzania (7.1% and 5.1%) (Magambo et al, ; Wajanga et al, ). We also compared our finding with studies in other developing countries like Indonesia (7.1%) (Ganiem et al, ), Vietnam (4%) (Smith et al, ), and Thailand (9.2%) (Pongsai, Atamasirikul, & Sungkanuparph, ).…”
Section: Discussionmentioning
confidence: 71%
“…Early studies on the CrAg LFA test showed high sensitivity and low specificity in urine. [7,8,9]. In other studies, the diluent was changed or the urine was frozen in order to improve specificity but the results didn’t reach the gold standard pattern (serum, CSF) [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Magambo and colleagues also noted a high prevalence of asymptomatic cryptococcal antigenemia in patients with CD4 count between 100 and 200. 19 This calls into question the use of 100 CD4 cells/mm 3 as a cutoff. However, very little data exists on the cost-effectiveness of screening patients with CD4 100-200 cells/mm 3 , and little is known about differences in development of CM and survival of patients in this range as compared with those with CD4<100 cells/mL.…”
Section: Discussionmentioning
confidence: 99%